Investigation on the ion diffusion and migration transport mechanism in Polypyrrole tri-layers actuators conducting polymer - Barzinjy, Azeez A.; Husham, Muhammad; Haji, Banaz S.; Jabbar, Kadhim Q. (Physics and Chemistry of Solid State, 2025)
Ion transference in conductive polymers has been initiated to rely equally upon material characterization and investigational circumstances. In the field of actuators, conductive polymers have been utilized with great success. This study employs the electrostatics module of the COMSOL Multiphysics finite element model to enhance existing modeling techniques and to comprehend the ion diffusion and migration transport mechanism in layered conductive polymers, specifically Polypyrrole tri-layers actuators. The model controls the specific flow pattern and temporal advancement of electrical voltage, cationic and anionic concentrations. The model uses only material characteristics to predict structural deformation in tri-layer actuators, indicating its potential practical utility. Moreover, it is sample-independent, making it valuable for electro-active polymer applications. Evaluation using existing data demonstrates that the simulation's predictions align with high certainty across the entire range of assessed input potentials, further validating its reliability and effectiveness.